Method for regulating Al / N value to improve forming performance of ultra-low carbon steel
AlN is added to smelting through vacuum induction furnace, and nitrogen atoms are fixed in the steel, which solves the problem of unstable nitrogen content control in ultra-low carbon steel smelting of arc furnace, improves the forming performance and material life, reduces production costs, and is suitable for industrial production of ultra-low carbon steel.
Patent Information
- Application Number
- CN202510674786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-29
AI Technical Summary
In the prior art, when smelting ultra-low carbon steel in an arc furnace, the nitrogen content is difficult to control below 30ppm, resulting in the steel aging and blue brittle phenomenon, affecting the forming performance, and the control cost is high and the efficiency is low, making it difficult to meet high quality standards.
Through vacuum induction furnace smelting, an appropriate amount of aluminum (Al) is added to generate AlN, fix the gap nitrogen atoms in the steel, regulate the Al/N value, enhance the recrystallized gamma texture, and improve the forming performance of ultra-low carbon steel.
Effectively reduce the solid solubility of free nitrogen atoms in steel, improve the r-value of plastic strain ratio, eliminate the yield platform, improve the forming performance and material life, reduce costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN120555860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-low carbon steel, and in particular to a method for regulating Al / N value to improve the formability of ultra-low carbon steel. Background Art
[0002] In recent years, the rapid development of the automotive industry has driven a surge in demand for automotive steel. To meet the needs of reducing vehicle weight, reducing material consumption, and conserving fuel, the quality requirements for automotive steel sheets have become increasingly stringent. Ultra-low carbon automotive steel, with its excellent deep-drawing properties, plastic strain resistance, and non-aging properties, is widely used in deep-drawn components such as automotive panels. Currently, cold-formed ultra-low carbon automotive steel features low carbon and nitrogen content (C 0.001-0.004%, N ≤ 0.004%). Elements such as Ti and Nb are also added to stabilize interstitial carbon and nitrogen atoms, ensuring excellent formability and enabling stamping into a variety of shapes. Based on the concepts of low carbon, green environmental protection, and the dual carbon strategy, green steel materials are emerging as a new demand for future development, adapting to reduced-volume, low-emission production, and lightweight applications. The use of electric arc furnaces to smelt ultra-low carbon automotive steel is a future trend.
[0003] However, the use of large amounts of scrap steel for electric arc furnace smelting will produce a large amount of residual elements and impurity elements due to the conditions of its raw materials, processes, and equipment. These elements are difficult to eliminate during the smelting process. As one of the elements that are difficult to eliminate during the electric arc furnace smelting process, the nitrogen element exists in the steel in a solid solution state, which will cause aging and blue brittleness of the steel. For ultra-low carbon automotive sheet steel, an increase in the nitrogen content is extremely unfavorable. Currently, with the advancement of vacuum technology, traditional converter long-process smelting can easily control the nitrogen content below 40 ppm, while for ultra-low carbon IF steel, the nitrogen content needs to be controlled below 30 ppm. The nitrogen content of ultra-low carbon steel smelted in domestic electric arc furnace short-process can generally be controlled to be less than 60 ppm. Some research teams can achieve an nitrogen content of less than 45 ppm by optimizing the denitrification process in the smelting process. It is difficult to achieve the standard of an nitrogen content below 30 ppm, and there is also the problem of unstable control of the nitrogen content of the product.
[0004] The characteristic parameters for evaluating ultra-low carbon cold-formed steel include: plastic strain ratio r value, work hardening index n value, earing parameter Δr, elongation after fracture, total elongation, etc. The plastic strain ratio r value reflects the thinning resistance of the metal sheet. The appearance of a yield platform during the stamping process will cause uneven deformation of the material, resulting in local unevenness in the thickness direction, avoiding cracking, and seriously affecting the forming performance of the material. The r value is closely related to the texture type in the steel. Development {111} <110> and {111} <112> The {111} / / ND type texture (γ texture) is conducive to the formation of a high r value, which is beneficial to deep drawing performance. The stronger the γ texture, the higher the r value. The free interstitial nitrogen atoms in the steel will weaken the γ texture components in the steel that are beneficial to formability. At the same time, the higher the solid solution nitrogen content, the greater the aging behavior of cold-formed stamping steel and the occurrence of yielding, which seriously affects the stamping performance of ultra-low carbon automotive steel and further reduces the plasticity, toughness and cold working properties of the steel. Therefore, elements such as Ti and Nb are usually added to ultra-low carbon cold-formed steel to fix the interstitial atoms C and N in the steel.
[0005] Chinese patent CN104630614A discloses a method for improving the forming performance of ultra-low carbon aluminum-killed steel galvanized products, wherein the nitrogen content is controlled below 30 ppm and the aluminum content is controlled below 600 ppm. Obviously, the control cost is high. It can be seen from its Examples 1-5 that the control of nitrogen content is not stable and the mechanical properties are not excellent. In particular, the strength-ductility product and yield strength of the prepared material are relatively low and cannot reach higher values; and the plastic strain ratio is higher than 1.9. The lower the deformation capacity of the material in the thickness direction, the greater the risk of local stress concentration and cracking.
[0006] Chinese patent CN103602889A discloses a strengthening and toughening process for ultra-low carbon steel with high carbon and manganese content, wherein the carbon content is high and a wide range of alloying elements are selected, and the strength and toughness are improved through temperature control treatments such as microstructure homogenization, high-temperature plastic deformation, controlled cooling, and medium-temperature isothermal treatment. This method does not consider the control of nitrogen content, and does not consider adding elements such as Ti and Nb to fix the interstitial atoms C and N in the steel. Although the heat treatment method can improve some mechanical properties to a certain extent, it cannot synergistically improve the stamping forming performance, plasticity, toughness and cold working performance of ultra-low carbon steel.
[0007] Therefore, in order to make the ultra-low carbon automotive steel produced by the electric arc furnace meet high quality standards, the yield platform caused by excessive nitrogen content, the reduction of plastic strain ratio r value and the weakening of forming performance are problems that need to be solved at present. Summary of the Invention
[0008] In order to solve the technical problems in the prior art such as uneven deformation and fracture tendency of ultra-low carbon steel containing a large amount of nitrogen during stamping and forming, which reduces the service life of the material, unstable control of nitrogen content in ultra-low carbon steel, difficulty in achieving the standard of nitrogen content below 30ppm, inability to achieve synergistic improvement of characteristic parameters of ultra-low carbon cold-formed steel, high control cost, low efficiency, low upper limit of mechanical properties of prepared ultra-low carbon cold-formed steel, and difficulty in achieving low-cost and high-efficiency process breakthroughs, the present invention proposes a method for regulating Al / N value to improve the forming performance of ultra-low carbon steel that can solve the above-mentioned technical problems. The technical solution is as follows:
[0009] A method for regulating the Al / N value to improve the formability of ultra-low carbon steel, the method comprising smelting, forging, hot rolling, cold rolling and annealing, and the specific process is as follows:
[0010] S1. Smelting and forging: A vacuum induction furnace is used to melt the ingot according to the set composition; the ingot is then forged into a forging blank, and then air-cooled to room temperature;
[0011] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment before rolling, rolled in the austenite region to obtain hot rolled plate, and then coiled and air-cooled to room temperature;
[0012] S3, cold rolling: the hot rolled plate in S2 is ground to remove the oxide scale and then subjected to multiple cold rolling passes to obtain the cold rolled plate;
[0013] S4, annealing: the cold-rolled sheet of S3 is subjected to annealing heat treatment to obtain an ultra-low carbon steel sheet.
[0014] Optionally, the mass percentage of each component of the ingot in S1 is: C<0.03%, Mn≤0.14%, Al 0.01-0.1%, N 0.0025-0.01%, and the rest are iron and residual elements, and the Al / N value is 6.2-40.
[0015] Optionally, the raw material of S1 is 99.9% pure iron, with different amounts of pure Al blocks added, and smelted in a vacuum induction furnace. N2 is introduced during the smelting process, the forging temperature is 850-1180°C, and the size of the forging billet is 25×25-35×35mm.
[0016] Optionally, the high temperature heat treatment of S2 has a holding temperature of 1180-1220° C. and a holding time of 1-1.5 h.
[0017] Optionally, the initial rolling temperature of the austenite region rolling of S2 is <1160°C, the final rolling temperature is >850°C, the rolling passes are 3, the total reduction is 73-76%, the coiling temperature is 700-800°C, and the coiling holding time is 30-45 minutes.
[0018] Optionally, the hot-rolled plate of S2 has a thickness of 7.4-8.0 mm.
[0019] Optionally, the cold rolling of S3 has 11-13 passes, with a reduction of 5-25% in each pass and a total reduction of 80-85%.
[0020] Optionally, the cold-rolled plate of S3 has a thickness of 1.1-1.4 mm and a hardness of 220-260 HRC.
[0021] Optionally, the annealing heat treatment temperature in S4 is 725-775° C., and the holding time is 30-60 min.
[0022] Optionally, the S4 ultra-low carbon steel plate has a hardness of 100-110 HRC, a tensile strength of 260-310 MPa, a yield strength of 100-220 MPa, a yield strength ratio of 0.39-0.73, an elongation after fracture of 34-52%, and a plastic strain ratio r value of 1.0-2.1.
[0023] The technical principle of the present invention: Al, as an element with a strong affinity with element N, easily reacts in steel to form AlN, thereby fixing the interstitial N atoms in the steel. Since the relative atomic mass of N is 14 and the relative atomic mass of Al is 27, it can be seen from the reaction of Al and N to form AlN that theoretically, about twice the Al content is required to fix N, so different Al elements are designed to be added to obtain different Al / N values. Adding different Al elements can reduce the number of interstitial N atoms in the steel, enhance the formation of recrystallized γ texture ({111} / / ND) during annealing, and reduce the strength of other unfavorable texture components. The plastic strain ratio r value is related to the strength of the recrystallized γ texture. The stronger the recrystallized γ texture, the higher the r value, the better the ductility, and it is less likely to cause uneven deformation and surface defects during the stamping process of ultra-low carbon steel.
[0024] Interstitial carbon and nitrogen atoms in new-generation ultra-low-carbon automotive steels (IF steels) are often fixed with elements such as Ti and Nb. However, Al also readily reacts with N to form AlN. Excessively large second-phase particles formed by Ti, Nb, and other elements to fix N can lead to cracking during rolling. Al is inexpensive and can be eliminated as a deoxidizing element in steelmaking during scrap recycling. The AlN precipitated by the addition of an appropriate amount of Al can transform the original austenite grains into pancake-shaped grains during annealing and recrystallization. This pancake-shaped grain is believed to be beneficial for the steel's stamping properties. Increasing the Al addition, and thus the Al / N ratio, reduces the dissolved nitrogen content in the steel and increases the size of the AlN precipitates. These coarse precipitates promote the formation of γ-texture ({111} / / ND) components during annealing and recrystallization, thereby increasing the r value.
[0025] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0026] The above scheme, the present invention proposes a method for regulating the Al / N value to improve the forming performance of ultra-low carbon steel, which can solve the technical problems in the prior art that ultra-low carbon steel containing more N has uneven deformation and fracture tendency during the stamping forming process, which reduces the service life of the material, the nitrogen content of ultra-low carbon steel is unstable, it is difficult to achieve the standard of N content below 30ppm, the characteristic parameters of ultra-low carbon cold-formed steel cannot be synergistically improved, the control cost is high, the efficiency is low, the upper limit of the mechanical properties of the prepared ultra-low carbon cold-formed steel is low, and it is difficult to obtain low-cost and high-efficiency process breakthroughs.
[0027] The present invention is based on the fact that Al is an element with a strong affinity with nitrogen in steel and is easy to form AlN. Al is economical and low in price. At the same time, it can be eliminated as a deoxidizing element in steelmaking during the recycling process of scrap steel. An appropriate amount of Al is added to the steel to form nitrogen-containing inclusions, thereby reducing the solid solution content of interstitial nitrogen atoms in the steel.
[0028] The method of the present invention reduces the adverse effects of N, is beneficial to enhancing the recrystallized γ texture ({111} / / ND) component, and reduces the formation of the non-γ texture ({111} / / ND) component.
[0029] The method of the present invention is beneficial to improving the plastic strain ratio r value of the forming performance indicator, eliminating the yield platform on the tensile curve, avoiding uneven deformation and fracture tendency of ultra-low carbon steel containing a large amount of nitrogen during the stamping forming process, reducing the service life of the material, and ensuring that the ultra-low carbon steel has good forming performance.
[0030] The method of the present invention can improve the performance and quality of ultra-low carbon automotive steel smelted in an electric arc furnace, further enhance the competitiveness and quality conditions of green steel materials in the market, and also provide a method for eliminating impurity nitrogen elements during the electric arc furnace smelting process.
[0031] In summary, compared with other traditional methods, the method of the present invention can effectively utilize the strong affinity between the alloying elements Al and N to quickly generate nitride AlN, which will reduce the solid solubility of free interstitial N atoms in the steel and improve the problem of weakened forming performance caused by excessive N elements. In addition, increasing the Al / N value can increase the size of the nitride precipitation phase, enhance the strength of the γ texture ({111} / / ND) component, and weaken the Goss texture ({100} <001> ) component strength, eliminates the yield platform of ultra-low carbon steel, and improves the elongation after fracture and the plastic strain ratio r value; the preparation method is simple and easy to operate, green and environmentally friendly, low cost, short process, high efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is an ODF cross-sectional view of φ2=45° obtained by using EBSD to detect the texture components of the ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 1 of the present invention;
[0034] Figure 2 is a stress-strain curve of an ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 1 of the present invention;
[0035] Figure 3 This is an ODF cross-sectional view of φ2=45° obtained by using EBSD to detect the texture components of the ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 2 of the present invention;
[0036] Figure 4 is a stress-strain curve of an ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 2 of the present invention;
[0037] Figure 5 This is an ODF cross-sectional view of φ2=45° obtained by using EBSD to detect the texture components of the ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 3 of the present invention;
[0038] Figure 6 is a stress-strain curve of an ultra-low carbon steel prepared by the preparation method of ultra-low carbon steel in Comparative Example 3 of the present invention;
[0039] Figure 7 This is an ODF cross-sectional view with a diameter of φ2 = 45° obtained by using EBSD to detect the texture components of the ultra-low carbon steel prepared by a method for regulating the Al / N value to improve the formability of ultra-low carbon steel in Example 1 of the present invention;
[0040] Figure 8 1 is a stress-strain curve of ultra-low carbon steel prepared by a method for regulating the Al / N value to improve the formability of ultra-low carbon steel according to Example 1 of the present invention;
[0041] Figure 9 This is an ODF cross-sectional view at φ2=45° obtained by using EBSD to detect the texture components of the ultra-low carbon steel prepared by a method for regulating the Al / N value to improve the formability of ultra-low carbon steel in Example 2 of the present invention;
[0042] Figure 10This is a stress-strain curve of ultra-low carbon steel prepared by a method for regulating the Al / N value to improve the formability of ultra-low carbon steel according to Example 2 of the present invention. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0044] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations, or explanations. Any embodiment or design described as an "exemplary" in the present invention should not be interpreted as being preferred or advantageous over other embodiments or designs. Rather, the use of the word "exemplary" is intended to present concepts in a concrete manner. Furthermore, in the embodiments of the present invention, "and / or" can mean both or either of the two.
[0045] In the embodiments of the present invention, “image” and “picture” may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are the same.
[0046] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.
[0047] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0048] A method for regulating the Al / N value to improve the formability of ultra-low carbon steel, the method comprising smelting, forging, hot rolling, cold rolling and annealing, and the specific process is as follows:
[0049] S1. Smelting and forging: A vacuum induction furnace is used to melt the ingot according to the set composition; the ingot is then forged into a forging blank, and then air-cooled to room temperature;
[0050] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment before rolling, rolled in the austenite region to obtain hot rolled plate, and then coiled and air-cooled to room temperature;
[0051] S3, cold rolling: the hot rolled plate in S2 is ground to remove the oxide scale and then subjected to multiple cold rolling passes to obtain the cold rolled plate;
[0052] S4, annealing: the cold-rolled sheet of S3 is subjected to annealing heat treatment to obtain an ultra-low carbon steel sheet.
[0053] In particular, the mass percentages of the components of the ingot in S1 are: C<0.03%, Mn≤0.14%, Al 0.01-0.1%, N 0.0025-0.01%, and the rest are iron and residual elements, and the Al / N value is 6.2-40.
[0054] In particular, the raw material of S1 is 99.9% pure iron, with different amounts of pure Al blocks added. It is smelted in a vacuum induction furnace, with N2 introduced during the smelting process. The forging temperature is 850-1180℃, and the size of the forging billet is 25×25-35×35mm.
[0055] In particular, the high temperature heat treatment of S2 has a holding temperature of 1180-1220° C. and a holding time of 1-1.5 h.
[0056] In particular, the initial rolling temperature of the austenite zone rolling of S2 is <1160℃, the final rolling temperature is >850℃, the rolling passes are 3, the total reduction is 73-76%, the coiling temperature is 700-800℃, and the coiling holding time is 30-45min.
[0057] In particular, the thickness of the hot rolled plate of S2 is 7.4-8.0 mm.
[0058] In particular, the cold rolling of S3 has 11-13 rolling passes, with a reduction of 5-25% in each pass and a total reduction of 80-85%.
[0059] In particular, the thickness of the cold-rolled plate of S3 is 1.1-1.4 mm, and the hardness of the cold-rolled plate is 220-260 HRC.
[0060] In particular, the annealing heat treatment temperature of S4 is 725-775° C., and the holding time is 30-60 min.
[0061] In particular, the hardness of S4 ultra-low carbon steel plate is 100-110HRC, the tensile strength is 260-310MPa, the yield strength is 100-220MPa, the yield strength ratio is 0.39-0.73, the elongation after fracture is 34-52%, and the plastic strain ratio r value is 1.0-2.1.
[0062] Test methods for related experiments
[0063] The tensile properties are tested in accordance with GB / T 1014.1-2018
[0064] The plastic strain ratio r value is tested in accordance with GB / T 5027-2016
[0065] Comparative Example 1
[0066] The present comparative example provides a method for preparing ultra-low carbon steel, which comprises smelting, forging, hot rolling, cold rolling and annealing. The specific process is as follows:
[0067] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.00%, N 0.0053%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 0 was obtained; the ingot was then kept at 1200°C for 2 hours and forged into a forging blank with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C, and then air-cooled to room temperature.
[0068] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling. The starting rolling temperature is less than 1160℃, the final rolling temperature is greater than 850℃, the rolling passes are 3, the total reduction is 75%, and the rolled plate is 7.5mm thick in the austenite region. The coiling temperature is 700℃, and the plate is kept at this temperature for 30min and then air-cooled to room temperature.
[0069] S3, cold rolling: the hot rolled plate of S2 is ground to remove the oxide scale and then subjected to multi-pass cold rolling of 7.0 mm thickness. The number of cold rolling passes is 12 times, the total reduction is 81.0%, and the cold rolled plate is 1.33 mm thick. The hardness of the cold rolled plate is 237 HRC.
[0070] S4, Annealing: Cut 10×8mm (ND×TD) samples and tensile specimens with a gauge length of 25mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8mm sample in a box furnace at 750℃-30min to fully recrystallize the cold-rolled structure; the tensile specimen with a gauge length of 25mm is annealed heat treatment in a box furnace at 750℃-120min to obtain an ultra-low carbon steel sheet.
[0071] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing. The polishing voltage is 20V and the polishing time is about 10s. After polishing, clean it with alcohol and dry it quickly with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data, and the ODF cross-section diagram of φ2=45° is obtained as shown below. Figure 1 Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and without obvious scratches; perform a tensile test on the ground specimen and obtain the stress-strain curve as shown in Figure 2 shown.
[0072] The ODF cross-section diagram of φ2=45° obtained in this comparative example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ) composition, the γ texture component that is beneficial to the formability is relatively weak, with a maximum strength of 3.8. The Goss texture component that is detrimental to the formability is very strong, with a maximum strength of 6.5.
[0073] Depend on Figure 2 It can be seen that a long yield platform appears on the stress-strain curve of the sample.
[0074] The hardness of the ultra-low carbon steel plate prepared in this comparative example is 104HRC. Figure 2 As shown, the tensile strength is 278 MPa, the yield strength is 204 MPa, the yield strength ratio is 0.734, the elongation after fracture is 38.2%, and the plastic strain ratio r value is 1.24.
[0075] Comparative Example 2
[0076] The present comparative example provides a method for preparing ultra-low carbon steel, which comprises smelting, forging, hot rolling, cold rolling and annealing. The specific process is as follows:
[0077] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.00%, N 0.008%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 0 was obtained; the ingot was then kept at 1200°C for 2 hours and then forged into a forging billet with a cross-section of 30 × 30 mm. The final forging temperature was greater than 850°C, and then air-cooled to room temperature.
[0078] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling. The starting rolling temperature is less than 1160℃, the final rolling temperature is greater than 850℃, the rolling passes are 3, the total reduction is 75%, and the rolled plate is 7.5mm thick in the austenite region. The coiling temperature is 700℃, and the plate is kept at this temperature for 30min and then air-cooled to room temperature.
[0079] S3, cold rolling: the hot rolled plate of S2 is ground to remove the oxide scale and then subjected to multi-pass cold rolling of 7.0 mm thickness. The number of cold rolling passes is 12 times, the total reduction is 80.1%, and the cold rolled plate is 1.39 mm thick. The hardness of the cold rolled plate is 256 HRC.
[0080] S4, Annealing: Cut 10×8mm (ND×TD) samples and tensile specimens with a gauge length of 25mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8mm sample in a box furnace at 750℃-30min to fully recrystallize the cold-rolled structure; the tensile specimen with a gauge length of 25mm is annealed heat treatment in a box furnace at 750℃-120min to obtain an ultra-low carbon steel sheet.
[0081] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing. The polishing voltage is 20V and the polishing time is about 10s. After polishing, clean it with alcohol and dry it quickly with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data, and the ODF cross-section diagram of φ2=45° is obtained as shown below. Figure 3 Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and without obvious scratches; perform a tensile test on the ground specimen and obtain the stress-strain curve as shown in Figure 4 shown.
[0082] The ODF cross-sectional view of φ2=45° obtained in this comparative example 2 is as follows Figure 1 As shown by Figure 3 It can be seen that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ) composition, the γ texture component that is beneficial to formability is very weak, with a maximum strength of 3.0. The Goss texture component that is detrimental to formability is very strong, with a maximum strength of 6.5.
[0083] Depend on Figure 4 It can be seen that a longer yield platform appears on the stress-strain curve of the sample.
[0084] The hardness of the ultra-low carbon steel plate prepared in this comparative example is 108HRC. Figure 4 As shown, the tensile strength is 304 MPa, the yield strength is 217 MPa, the yield strength ratio is 0.714, the elongation after fracture is 34.2%, and the plastic strain ratio r value is 1.01.
[0085] Comparative Example 3
[0086] The present comparative example provides a method for preparing ultra-low carbon steel, which comprises smelting, forging, hot rolling, cold rolling and annealing. The specific process is as follows:
[0087] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.093%, N 0.0055%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 1.7 was obtained. The ingot was then kept at 1200°C for 2 hours and forged into a forging blank with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C and then air-cooled to room temperature.
[0088] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the rolled plate is 7.5mm thick in the austenite region, the coiling temperature is 700℃, and after holding for 30min, it is air-cooled to room temperature;
[0089] S3, cold rolling: the hot rolled plate of S2 is ground to remove the oxide scale and then subjected to multi-pass cold rolling of 7.0 mm thickness. The number of cold rolling passes is 12 times, and the total reduction is 80.5%, to obtain a 1.36 mm thick cold rolled plate with a hardness of 243 HRC;
[0090] S4, Annealing: Cut 10×8mm (ND×TD) samples and tensile specimens with a gauge length of 25mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8mm sample in a box furnace at 750℃-30min to fully recrystallize the cold-rolled structure; the tensile specimen with a gauge length of 25mm is annealed heat treatment in a box furnace at 750℃-120min to obtain an ultra-low carbon steel sheet.
[0091] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing. The polishing voltage is 20V and the polishing time is about 10s. After polishing, clean it with alcohol and dry it quickly with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data, and the ODF cross-section diagram of φ2=45° is obtained as shown below. Figure 5Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and without obvious scratches; perform a tensile test on the ground specimen and obtain the stress-strain curve as shown in Figure 6 shown.
[0092] The ODF cross-sectional view of φ2=45° obtained in this comparative example 3 is as follows Figure 1 As shown by Figure 1 It can be seen that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ) composition, the maximum strength of the γ texture component which is beneficial to the formability is 3.44, and the Goss texture component which is not conducive to the formability is very strong, with a maximum strength of 7.4.
[0093] Depend on Figure 6 It can be seen that a longer yield platform appears on the stress-strain curve of Comparative Example 3. Figure 1-4 It can be seen that the strength of the γ texture component of this comparative example is almost unchanged, but the Goss texture component is still relatively strong, the yield platform is not shortened, and the elongation after fracture and the r value are slightly improved.
[0094] The hardness of the ultra-low carbon steel plate prepared in this comparative example 3 is 107HRC. Figure 6 As shown, the tensile strength is 278 MPa, the yield strength is 188 MPa, the yield strength ratio is 0.676, the elongation after fracture is 41.3%, and the plastic strain ratio r value is 1.39.
[0095] Example 1
[0096] The present embodiment provides a method for regulating the Al / N value to improve the formability of ultra-low carbon steel. The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling, and annealing. The specific process is as follows:
[0097] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.031%, N 0.0050%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 6.2 was obtained. The ingot was then kept at 1200°C for 2 hours and forged into a forging billet with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C and then air-cooled to room temperature.
[0098] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the plate is rolled into 7.5mm thick plate in the austenite region, the coiling temperature is 700℃, and after holding for 30min, it is air-cooled to room temperature;
[0099] S3, cold rolling: after the hot rolled plate in S2 is descaled, the 7.0 mm thick hot rolled plate is subjected to multiple cold rolling passes, the number of cold rolling passes is 12 times, the total reduction is 80.7%, and a 1.35 mm thick cold rolled plate is obtained. The hardness of the cold rolled plate is 236 HRC;
[0100] S4, annealing: Cut 10×8 mm (ND×TD) samples and tensile specimens with a gauge length of 25 mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8 mm sample in a box furnace at 750°C for 30 min to fully recrystallize the cold-rolled structure; and perform annealing heat treatment of the tensile specimen with a gauge length of 25 mm in a box furnace at 750°C for 120 min to obtain an ultra-low carbon steel sheet;
[0101] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing. The polishing voltage is 20V and the polishing time is about 10s. After polishing, clean it with alcohol and dry it quickly with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data, and the ODF cross-section diagram of φ2=45° is obtained as shown below. Figure 7 Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and without obvious scratches; perform a tensile test on the ground specimen and obtain the stress-strain curve as shown in Figure 8 shown.
[0102] The ODF cross-section diagram of φ2=45° obtained in Example 1 is as follows Figure 7 As shown by Figure 7 It can be seen that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ), the maximum strength of the γ texture component that is beneficial to the formability is 4.3. The maximum strength of the Goss texture component that is not conducive to the formability is 4.2. Figure 8 It can be seen that the yield platform on the stress-strain curve of Example 4 basically disappears. Figure 1-6 It can be seen that the γ texture component of Example 4 is significantly enhanced and the yield platform basically disappears.
[0103] The hardness of the ultra-low carbon steel plate prepared in this embodiment is 104HRC. Figure 8 As shown, the tensile strength is 294 MPa, the yield strength is 154 MPa, the yield strength ratio is 0.524, the elongation after fracture is 47.8%, and the plastic strain ratio r value is 1.56.
[0104] Example 2
[0105] The present embodiment provides a method for regulating the Al / N value to improve the formability of ultra-low carbon steel. The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling, and annealing. The specific process is as follows:
[0106] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.08%, N 0.0058%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 13.8 was obtained. The ingot was then kept at 1200°C for 2 hours and forged into a forging billet with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C, and then air-cooled to room temperature.
[0107] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the plate is rolled into 7.5mm thick plate in the austenite region, the coiling temperature is 700℃, and after holding for 30min, it is air-cooled to room temperature;
[0108] S3, cold rolling: after the hot rolled plate in S2 is descaled, the 7.0 mm thick hot rolled plate is subjected to multiple cold rolling passes, the number of cold rolling passes is 12, the total reduction is 83.6%, and the 1.16 mm thick cold rolled plate is obtained. The hardness of the cold rolled plate is 245 HRC;
[0109] S4, annealing: Cut 10×8 mm (ND×TD) samples and tensile specimens with a gauge length of 25 mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8 mm sample in a box furnace at 750°C for 30 min to fully recrystallize the cold-rolled structure; and perform annealing heat treatment of the tensile specimen with a gauge length of 25 mm in a box furnace at 750°C for 120 min to obtain an ultra-low carbon steel sheet;
[0110] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing. The polishing voltage is 20V and the polishing time is about 10s. After polishing, clean it with alcohol and dry it quickly with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data, and the ODF cross-section diagram of φ2=45° is obtained as shown below. Figure 9 Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and without obvious scratches; perform a tensile test on the ground specimen and obtain the stress-strain curve as shown in Figure 10 shown.
[0111] The ODF cross-section diagram of φ2=45° obtained in Example 2 is as follows: Figure 9 As shown by Figure 9 It can be seen that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ), the maximum strength of the γ texture component that is beneficial to the formability is 7.1, and the maximum strength of the Goss texture component that is not conducive to the formability is 2.5. Figure 10 It can be seen that the yield platform of the stress-strain curve of Example 5 disappears. Figure 1-8 It can be seen that the γ texture component of Example 2 is the strongest, and the strength of the Goss texture component continues to weaken, the yield platform disappears, and the formability is significantly improved.
[0112] The hardness of the ultra-low carbon steel plate prepared in Example 2 is 105HRC. Figure 10 As shown, the tensile strength is 305MPa, the yield strength is 159MPa, the yield strength ratio is 0.521, the elongation after fracture is 47.8%, and the plastic strain ratio r value is 1.81.
[0113] The formability of ultra-low carbon steel is related to the strength of the γ texture ({111} / / ND) in the steel. For good formability, γ texture is the most ideal crystal component. This type of texture provides the most suitable orientation for the slip system, making the strength in the thickness direction greater than the horizontal direction, which is conducive to the formation of a high r-value and beneficial for deep drawing performance. The stronger the γ texture, the higher the r-value. Goss texture results in relatively low strength in the direction perpendicular to rolling, that is, the thickness direction, resulting in poor resistance to thinning and a low r-value. Eliminating the yield plateau allows the sample to deform evenly during the stamping process, reducing the tendency to crack and increasing the service life of the material.
[0114] The EBSD and tensile test data from Comparative Examples 1-3 and Examples 1-2 indicate that, when using the process of the present invention to prepare ultra-low carbon steel, the strength of the γ texture component increases with increasing Al / N ratios, leading to higher elongation after fracture and improved plastic strain ratio r. At an Al / N ratio of 6.2, the yield plateau on the tensile curve nearly disappears, and at an Al / N ratio of 16.7, the overall formability is optimal. Increasing the Al / N ratio effectively improves formability.
[0115] Example 3
[0116] The present embodiment provides a method for regulating the Al / N value to improve the formability of ultra-low carbon steel. The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling, and annealing. The specific process is as follows:
[0117] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was as follows: C < 0.03%, Mn ≤ 0.14%, Al 0.03%, N 0.0031%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 9.7 was obtained. The ingot was then kept at 1200°C for 2 hours and forged into a forging blank with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C and then air-cooled to room temperature.
[0118] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the plate is rolled into 7.5mm thick plate in the austenite region, the coiling temperature is 700℃, and after holding for 30min, it is air-cooled to room temperature;
[0119] S3, cold rolling: after the hot-rolled plate in S2 is descaled, the 7.0 mm thick hot-rolled plate is subjected to multiple cold rolling passes, with 12 cold rolling passes and a total reduction of 82.0%, to obtain a 1.26 mm thick cold-rolled plate with a hardness of 231 HRC;
[0120] S4, annealing: Cut 10×8 mm (ND×TD) samples and tensile specimens with a gauge length of 25 mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8 mm sample in a box furnace at 750°C for 30 min to fully recrystallize the cold-rolled structure; and perform annealing heat treatment of the tensile specimen with a gauge length of 25 mm in a box furnace at 750°C for 120 min to obtain an ultra-low carbon steel sheet;
[0121] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing with a polishing voltage of 20V and polishing for about 10s. After polishing, clean it with alcohol and quickly dry it with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data and obtain an ODF cross-section image of φ2=45°. Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and free of obvious scratches; perform a tensile test on the ground sample to obtain a stress-strain curve.
[0122] The ODF cross-section at φ2 = 45° obtained in Example 3 shows that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ), the maximum strength of the γ texture component, which is beneficial to formability, reached 5.2, while the maximum strength of the Goss texture component, which is detrimental to formability, reached 3.8. The yield plateau in the stress-strain curve of Example 3 disappears. In Example 3, the γ texture component is enhanced, the strength of the Goss texture component continues to weaken, and the yield plateau disappears, significantly improving formability.
[0123] The ultra-low carbon steel plate prepared in this embodiment has a hardness of 104 HRC, a tensile strength of 273 MPa, a yield strength of 128 MPa, a yield strength ratio of 0.469, an elongation after fracture of 46.3%, and a plastic strain ratio r value of 1.51.
[0124] Example 4
[0125] The present embodiment provides a method for regulating the Al / N value to improve the formability of ultra-low carbon steel. The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling, and annealing. The specific process is as follows:
[0126] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.031%, N 0.0050%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 6.2 was obtained. The ingot was then kept at 1200°C for 2 hours and forged into a forging billet with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C and then air-cooled to room temperature.
[0127] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the plate is rolled into 7.5mm thick plate in the austenite region, the coiling temperature is 800℃, and after holding for 30min, it is air-cooled to room temperature;
[0128] S3, cold rolling: after the hot-rolled plate in S2 is descaled, the 7.0 mm thick hot-rolled plate is subjected to multiple cold rolling passes. The number of cold rolling passes is 12 times, and the total reduction is 82.0%, to obtain a 1.26 mm thick cold-rolled plate with a hardness of 233 HRC;
[0129] S4, annealing: Cut 10×8 mm (ND×TD) samples and tensile specimens with a gauge length of 25 mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8 mm sample in a box furnace at 750°C for 30 min to fully recrystallize the cold-rolled structure; and perform annealing heat treatment of the tensile specimen with a gauge length of 25 mm in a box furnace at 750°C for 120 min to obtain an ultra-low carbon steel sheet;
[0130] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing with a polishing voltage of 20V and polishing for about 10s. After polishing, clean it with alcohol and quickly dry it with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data and obtain an ODF cross-section image of φ2=45°. Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and free of obvious scratches; perform a tensile test on the ground sample to obtain a stress-strain curve.
[0131] The ODF cross-section at φ2 = 45° obtained in Example 4 shows that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ), the maximum strength of the γ texture component, which is beneficial to formability, is 5.2, while the maximum strength of the Goss texture component, which is detrimental to formability, is 4.4. The yield plateau in the stress-strain curve of Example 4 disappears. In Example 4, the γ texture component is enhanced, the strength of the Goss texture component does not change much, and the yield plateau disappears, significantly improving formability.
[0132] The ultra-low carbon steel plate prepared in this embodiment has a hardness of 106 HRC, a tensile strength of 268 MPa, a yield strength of 127 MPa, a yield strength ratio of 0.474, an elongation after fracture of 58.4%, and a plastic strain ratio r value of 1.84.
[0133] Example 5
[0134] The present embodiment provides a method for regulating the Al / N value to improve the formability of ultra-low carbon steel. The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling, and annealing. The specific process is as follows:
[0135] S1. Smelting and forging: A 5 kg ingot was obtained by melting in a vacuum induction furnace according to the set composition. The mass percentage of each component was: C < 0.03%, Mn ≤ 0.14%, Al 0.08%, N 0.0058%, and the rest was Fe and residual elements. The original ingot of the sample with an Al / N ratio of 13.8 was obtained. The ingot was then kept at 1200°C for 1 hour and forged into a forging blank with a cross-section of 30 × 30 mm. The final forging temperature was > 850°C and then air-cooled to room temperature.
[0136] S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment at 1200℃ for 1h before rolling, and then enters the rolling mill for hot rolling, with the starting rolling temperature less than 1160℃, the final rolling temperature greater than 850℃, the rolling pass number is 3, the total reduction is 75%, and the plate is rolled into 7.5mm thick plate in the austenite region, the coiling temperature is 800℃, and after holding for 30min, it is air-cooled to room temperature;
[0137] S3, cold rolling: after the hot-rolled plate in S2 is descaled, the 7.0 mm thick hot-rolled plate is subjected to multiple cold rolling passes, with 12 cold rolling passes and a total reduction of 83.7%, to obtain a 1.14 mm thick cold-rolled plate with a hardness of 227 HRC;
[0138] S4, annealing: Cut 10×8 mm (ND×TD) samples and tensile specimens with a gauge length of 25 mm from the cold-rolled sheet of S3, and perform annealing heat treatment of the 10×8 mm sample in a box furnace at 750°C for 30 min to fully recrystallize the cold-rolled structure; and perform annealing heat treatment of the tensile specimen with a gauge length of 25 mm in a box furnace at 750°C for 120 min to obtain an ultra-low carbon steel sheet;
[0139] S5. Sample preparation: Use 600#, 1000#, 2000#, 3000#, and 5000# water-abrasive sandpaper to grind the ND×TD surface of the heat-treated sample until the surface is smooth and free of obvious scratches. Then use a 10% perchloric acid solution (perchloric acid: alcohol = 1:9) for electrolytic polishing with a polishing voltage of 20V and polishing for about 10s. After polishing, clean it with alcohol and quickly dry it with a hair dryer. Use a field emission scanning electron microscope equipped with an Oxford Aztec EBSD device to characterize the structure of the ND×TD surface of the sample. The microstructure of four areas of 1000μm×750μm is measured with a step size of 3μm. After the characterization is completed, the four exported files are spliced using MapStitcher software to observe the macro texture of the sample. Channel 5 software is used to analyze the data and obtain an ODF cross-section image of φ2=45°. Use 240#, 1000#, and 2000# sandpaper to grind off the oxide scale on the surface and side of the heat-treated tensile specimen until the surface is smooth and free of obvious scratches; perform a tensile test on the ground sample to obtain a stress-strain curve.
[0140] The ODF cross-section at φ2 = 45° obtained in Example 5 shows that the texture is mainly composed of γ texture ({111} / / ND) and Goss texture ({100} <001> ), the maximum strength of the γ texture component, which is beneficial to formability, reaches 7.8, while the maximum strength of the Goss texture component, which is detrimental to formability, reaches 1.0. The yield plateau in the stress-strain curve of Example 5 disappears. In Example 5, the γ texture component is enhanced, while the strength of the Goss texture component continues to weaken, resulting in the disappearance of the yield plateau and a significant improvement in formability.
[0141] The ultra-low carbon steel plate prepared in this embodiment has a hardness of 103HRC, a tensile strength of 273MPa, a yield strength of 108MPa, a yield strength ratio of 0.396, an elongation after fracture of 44.8%, and a plastic strain ratio r value of 2.01.
[0142] By comparing Comparative Examples 1-3 with Examples 1-5, it was found that increasing the Al / N value and the coiling temperature can effectively enhance the recrystallized γ texture of ultra-low carbon steel and weaken the Goss texture components that are detrimental to the formability. At the same time, it eliminates the yield platform on the stress-strain curve, reduces the yield strength ratio, increases the plastic strain ratio and elongation after fracture, and significantly improves the formability.
[0143] The above scheme, the present invention proposes a method for regulating the Al / N value to improve the forming performance of ultra-low carbon steel, which can solve the technical problems in the prior art that ultra-low carbon steel containing more N has uneven deformation and fracture tendency during the stamping forming process, which reduces the service life of the material, the nitrogen content of ultra-low carbon steel is unstable, it is difficult to achieve the standard of N content below 30ppm, the characteristic parameters of ultra-low carbon cold-formed steel cannot be synergistically improved, the control cost is high, the efficiency is low, the upper limit of the mechanical properties of the prepared ultra-low carbon cold-formed steel is low, and it is difficult to obtain low-cost and high-efficiency process breakthroughs.
[0144] The present invention is based on the fact that Al is an element with a strong affinity with nitrogen in steel and is easy to form AlN. Al is economical and low in price. At the same time, it can be eliminated as a deoxidizing element in steelmaking during the recycling process of scrap steel. An appropriate amount of Al is added to the steel to form nitrogen-containing inclusions, thereby reducing the solid solution content of interstitial nitrogen atoms in the steel.
[0145] The method of the present invention reduces the adverse effects of N, is beneficial to enhancing the recrystallized γ texture ({111} / / ND) component, and reduces the formation of the non-γ texture ({111} / / ND) component.
[0146] The method of the present invention is beneficial to improving the plastic strain ratio r value of the forming performance indicator, eliminating the yield platform on the tensile curve, avoiding uneven deformation and fracture tendency of ultra-low carbon steel containing a large amount of nitrogen during the stamping forming process, reducing the service life of the material, and ensuring that the ultra-low carbon steel has good forming performance.
[0147] The method of the present invention can improve the performance and quality of ultra-low carbon automotive steel smelted in an electric arc furnace, further enhance the competitiveness and quality conditions of green steel materials in the market, and also provide a method for eliminating impurity nitrogen elements during the electric arc furnace smelting process.
[0148] In summary, compared with other traditional methods, the method of the present invention can effectively utilize the strong affinity between the alloying elements Al and N to quickly generate nitride AlN, which will reduce the solid solubility of free interstitial N atoms in the steel and improve the problem of weakened forming performance caused by excessive N elements. In addition, increasing the Al / N value can increase the size of the nitride precipitation phase, enhance the strength of the γ texture ({111} / / ND) component, and weaken the Goss texture ({100} <001> ) component strength, eliminates the yield platform of ultra-low carbon steel, and improves the elongation after fracture and the plastic strain ratio r value; the preparation method is simple and easy to operate, green and environmentally friendly, low cost, short process, high efficiency, and is conducive to large-scale industrial production and promotion.
[0149] It should be understood that the term "and / or" as used herein simply describes a relationship between associated objects, indicating that three possible relationships exist. For example, "A and / or B" can represent: A alone, A and B together, or B alone. A and B can be singular or plural. Furthermore, the character " / " as used herein generally indicates an "or" relationship between the associated objects, but it may also indicate an "and / or" relationship. For specific understanding, please refer to the context.
[0150] In this disclosure, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or plural.
[0151] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0152] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A method for regulating the Al / N value to improve the formability of ultra-low carbon steel, characterized in that: The method for regulating the Al / N value to improve the formability of ultra-low carbon steel includes smelting, forging, hot rolling, cold rolling and annealing, and the specific process is as follows: S1. Smelting and forging: A vacuum induction furnace is used to melt the ingot according to the set composition; the ingot is then forged into a forging blank, and then air-cooled to room temperature; S2, hot rolling: The S2 forging billet is subjected to high temperature heat treatment before rolling, rolled in the austenite region to obtain hot rolled plate, and then coiled and air-cooled to room temperature; S3, cold rolling: the hot rolled plate in S2 is ground to remove the oxide scale and then subjected to multiple cold rolling passes to obtain the cold rolled plate; S4, annealing: the cold-rolled sheet of S3 is subjected to annealing heat treatment to obtain an ultra-low carbon steel sheet.
2. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The mass percentage of each component in the ingot S1 is: C<0.03%, Mn≤0.14%, Al 0.01-0.1%, N 0.0025-0.01%, and the rest are iron and residual elements, and the Al / N value is 6.2-40.
3. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The raw material of S1 is 99.9% pure iron, with different amounts of pure Al blocks added. It is smelted in a vacuum induction furnace with N2 introduced during the smelting process. The forging temperature is 850-1180℃, and the size of the forging blank is 25×25-35×35mm.
4. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The holding temperature of the high temperature heat treatment of S2 is 1180-1220°C, and the holding time is 1-1.5h.
5. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The initial rolling temperature of S2 in the austenite zone is <1160℃, the final rolling temperature is >850℃, the rolling passes are 3, the total reduction is 73-76%, the coiling temperature is 700-800℃, and the coiling holding time is 30-45min.
6. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The thickness of S2 hot rolled plate is 7.4-8.0mm.
7. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The number of cold rolling passes of S3 is 11-13, the reduction in each pass is 5-25%, and the total reduction is 80-85%.
8. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The thickness of S3 cold rolled plate is 1.1-1.4mm, and the hardness of cold rolled plate is 220-260HRC.
9. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The annealing heat treatment temperature of S4 is 725-775°C, and the holding time is 30-60 minutes.
10. The method for improving the formability of ultra-low carbon steel by regulating the Al / N value according to claim 1, characterized in that: The hardness of S4 ultra-low carbon steel plate is 100-110HRC, the tensile strength is 260-310MPa, the yield strength is 100-220MPa, the yield strength ratio is 0.39-0.73, the elongation after fracture is 34-52%, and the plastic strain ratio r value is 1.0-2.1.
Citation Information
Patent Citations
Strengthening and toughening process for ultra-low carbon steel with relatively high carbon and manganese contents
CN103602889A
Method for improving forming performance of super-low-carbon aluminum killed steel galvanized product
CN104630614A